Why Does Poverty Persist in Madura, Indonesia? Evidence from Human Development and Educational Empowerment Perspectives - Kamalia Putri Ulfa; Wardoyo Dewie Tri Wijayati; Aji Tony Seno; Arifin Syamsul; Muhlisin Muhlisin (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
Why does poverty remain persistently high in Madura, Indonesia, despite ongoing improvements in socio-economic development and educational access? This study investigates the determinants of poverty from human development and educational empowerment perspectives by examining the roles of the Human Development Index (HDI), unemployment, household consumption, and regional income. The findings reveal that improvements in human development significantly reduce poverty, highlighting the importance of educational attainment, health conditions, and human capability enhancement in promoting welfare. Household consumption also exhibits a significant relationship with poverty, suggesting that household welfare and purchasing capacity remain important determinants of poverty outcomes. In contrast, unemployment and regional income do not have statistically significant effects on poverty, indicating that labor market status and aggregate economic growth alone are insufficient to explain poverty persistence in Madura. These findings suggest that poverty reduction depends not only on economic expansion but also on the capacity of individuals and communities to convert available opportunities into sustainable welfare improvements. The study contributes to the literature on poverty, human development, and educational empowerment by demonstrating the central role of human capability formation in addressing persistent poverty. The findings further highlight the importance of strengthening educational empowerment, human capital development, and community capability as key policy priorities for achieving inclusive and sustainable poverty reduction in peripheral regions.